Perancangan Evaporator Jenis Tube In Tube Heat Exchanger Pada Sistem Adsorpsi Kapasitas 5000 BTU/h Dengan Pasangan Karbon Aktif-Metanol Sebagai Adsorben-Adsorbat - Johannes Panjaitan; Awaludin Martin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Global warming and high electrical energy consumption issues have been attention all human in the world. Among various technologies especially refrigeration that being developed to prevent those problem. The refrigeration vapor compression cycle, which impaction on the ozone layer and potential damage of global warming because contains HCFC and CFC and Beside that, the highly electrical energy consumption might be happen. In this research proposed a designing and manufacturing of adsorption cooling system with a double bed adsorbed with capacity 5000 Btu/h. The methanol was used as adsorption and activated carbon as adsorbent, which have characteristic zero Ozone Depletion Potential (ODP) and zero Global Warming Potential (GWP) that was expected to be able to decrease damage to the ozone layer and minimize the electrical energy consumption. The method used in this research was the design. The adsorption cooling system contained two adsorbed in a U-tube and circular plate fin with tube from copper and circular plate fin structure from aluminum which a distance fins of 5 mm. An evaporator and a condenser (tube in tube of heat exchanger) with a tube from copper with total heat transfer area was 0.457 m² for evaporator, with desorption/ adsorption phase time was 20 minutes.Keywords: Adsorption, Methanol, Evaporator, Activated Carbon.